DESAIN PERMAINAN ULAR TANGGA DALAM PEMBELAJARAN KIMIA - Silvia P Ningsih; Amilda Amilda; Etrie Jayanti (Chemistry Education Department of Education and Teaching Faculty, 2021)
The limitations of media variants and the infrequent use of learning media in the chemistry learning process in one of the public schools in Palembang City are the main problems behind the research. This research was an R&D (research and development) research that aimed to develop snakes and ladders game on acid-base topic, determine validity based on expert judgment, determine the practicality of media based on student response questionnaire assessments, and determine the effectiveness of the learning media. The development of the snake and ladder game learning media followed the ADDIE development framework. The validators in this study were content experts, media experts, and education practitioners. The subjects were students in one of the public schools in the Palembang City. Data collection instruments used validation sheets, student response questionnaires, and test questions. The results of the validity test got an average score of 4,07 meaning that it was feasible. The practicality assessment in small-scale trials got 94,86% which was included in the very practical category, the medium-scale trials of 90,75% and also included in the very practical category. The results of test showed an increase in student learning outcomes. It could be proved by the average post-test score of the experimental group students was 85,12 while the average post-test score of the control group was 78,12 and the Sig. (2-tailed) of the t-test (independent sample t-test) had 0,000 < 0,05, which means the snake and ladder game learning media developed is effective to improve student learning outcomes.